Implementasi Sistem Pakar menggunakan Metode Certainty factor Untuk Mendiagnosa Penyakit Herpes Zoster - Ikhsan Romli; E Romansyah; Andika Permana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
Herpes Zoster is a skin disease that is very difficult to treat and everyone can certainly experience it, the characteristics of this disease are characterized by unilateral vesicles in groups with pain characterized by radicular around the dermatome. This study aims to establish a Web-based Certainty factor method as a tool to diagnose skin diseases. With this application, it doesnâ€™t need long time to find out what type of herpes zoster is suffering. To use this applicationÂ  is that the patient answers the questions which are provided by the system, then the system will process all the patient answers using the certainty factor method, after that, the system will produce output as the results of the diagnosis of the type of shingles. The system built can help patients to know the type of disease that is being suffered by the patients and in accordance with expert analysis of skin diseases.